Evaluation of initial prestress state in PS strand using the deformation characteristics of multi-strand anchor head - Park, Jang Ho; Cho, Jeong Rae; Choo, Jinkyo F. (KSCE Journal of Civil Engineering, 2018)
Prestressed concrete (PSC) bridge resists to deflection and cracking by prestressing its concrete superstructure using steel strands. The initial prestress force introduced in the strands at the completion of the structure influences sensitively its long-term performance. Rating the health of the PSC bridge should thus start with the knowledge of this initial prestress. However, the measurements given by the hydraulic jack and load cell used during prestressing may not be absolute indicators of the effective stress introduced in the strands. Considering that the strain distribution in the anchor can be used to measure the prestress in the strands and that the anchor head is the most accessible part of the PSC member, this study presents a method using the deformation characteristics of the anchor head to evaluate the initial prestress of the strands. To that goal, experimental and numerical analyses were performed on an anchorage-strand system considering the coefficient of friction between the wedge and the anchor head. The results show that the variation of the hoop strain measured in the multi-strand anchor head can be used to evaluate effectively the initial prestress state of the strands with respect to the applied jacking force.
Keywords: Deformation Characteristics; Hoop strain; Initial prestress; multi-strand anchor head; Prestress forces; deformation characteristics; hoop strain; initial prestress state; multi-strand anchor head; prestress force